Shu-hsien Liu. Essentials of Contemporary Neo-Confucian Philosophy, Resources in Asian philosophy and religion - Silius, Vytis (Acta Orientalia Vilnensia, 2007)
Shu-hsien Liu. Essentials of Contemporary Neo-Confucian Philosophy, Resources in Asian philosophy and religion, Westport, London: Praeger, 2003, pp. xv+165. ISBN 0-313-27581-5 (HB)
Keywords: -